Analisis Tingkat Keramah Lingkungan Alat Tangkap Jaring Insang Hanyut (Drift gillnet) di Perairan Lekok Kabupaten Pasuruan - Heni Wardania Rakhma; M Tajudin Noor; Exist Saraswati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Fishing activities are very worrying, due to fishing activities using fishing gear that is not environmentally friendly and not managed well, which can trigger resource damage in the future. This research aims to analyze the status of fishing gear based on environmentally friendly fishing gear categories and fishing units in accordance with the Code of Conduct for Responsible Fisheries (CCRF). The research method used is a survey method and data collected through a process of field observation, interviews and questionnaires. The environmental friendliness of the Drift gillnet fishing gear has a value of 912 with a weight score of 30.40. The catches include Kembung, yellow selar, manyung, peperek, kuniran, gulamah, kerong, layur, mullet, talang-talang, tetengek, black pomfret, kurau, aru-aru, Sembilang, coral grouper, mud grouper. The catch rate value was 28 in November, while December had a catch rate value of 21,167.